Forecasting Strategies for Haboobs: An Underreported Weather Phenomenon - Mark J. Dempsey (Advances in Meteorology)
On June 5, 2013, Lubbock Texas is hit by a haboob at 10:30 pm. The storm is categorized as a wind event by television media and the dust component goes unreported. This event is used as a case study to evaluate the usefulness of the polarimetric variables differential reflectivity (ZDR) and correlation coefficient (CC) in identifying the storm as a haboob. Photographic evidence of the haboob is collected and correlated to NEXRAD signatures of base reflectivity and velocity from the Lubbock TX NEXRAD station (KLBB). NEXRAD level III products ZDR and CC are also obtained. The storm presents with gust front features to the north and east of the station. Low values returned from CC indicate nonmeteorological content. ZDR representations weakly indicate the presence of gust fronts to the east, with a stronger signal to the north. As no visual evidence of the northern gust front is available, the ZDR data are inconclusive. The correlation of low CC values to the visual representation of the haboob is an indicator that CC in combination with the NEXRAD base reflectivity and velocity products may be used to test wind events for the presence of sand, dust, and dirt and therefore exhibit predictive qualities.